Preaching about the Last judgment in the New Testament? : a hermeneutical approach to the portrayal of the Last Judgment in Luk 16:19-31 and Rev 20:11-15 - Kuenstel, Annegret (Stellenbosch : Stellenbosch University, 2011)
Assignment (MDiv)--Stellenbosch University, 2006.